2009
DOI: 10.1369/jhc.2009.954727
|View full text |Cite
|
Sign up to set email alerts
|

DNA Content Differences Between Male and Female Chicken (Gallus gallus domesticus) Nuclei and Z and W Chromosomes Resolved by Image Cytometry

Abstract: S U M M A R Y Chicken red blood cells (CRBCs) are widely used as standards for DNA content determination. Cytogenetic data have shown that the Z sex chromosome is approximately twice as large as the W, so that the DNA content differs to some extent between male (ZZ) and female (ZW) chickens. Despite this fact, male and female CRBCs have been indiscriminately used in absolute genome size determination. Our work was conducted to verify whether the DNA content differences between male and female Gallus gallus dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Using trout blood as the internal standard, the haploid female chicken genome size (GS) determined by flow cytometry was 1.05 Gb (1.07 pg) as previously reported for female chicken [59]. We preferred rainbow trout nuclei as the internal standard in the assessment of the Artemia GS because their fluorescence values did not overlap with those of Artemia , as was the case with fluorescence values obtained from chicken nuclei.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Using trout blood as the internal standard, the haploid female chicken genome size (GS) determined by flow cytometry was 1.05 Gb (1.07 pg) as previously reported for female chicken [59]. We preferred rainbow trout nuclei as the internal standard in the assessment of the Artemia GS because their fluorescence values did not overlap with those of Artemia , as was the case with fluorescence values obtained from chicken nuclei.…”
Section: Resultsmentioning
confidence: 96%
“…The haploid genome size (GS) of Artemia was assessed against the rainbow trout (haploid GS 2.4–3.0 pg or 2.35−2.93 Gb [58]) and the chicken genome (haploid GS 1.07 pg or 1.05 Gb [59]), both used as internal standards.…”
Section: Methodsmentioning
confidence: 99%
“…DAPI-stained nuclei were analyzed at a flow rate of 100 nuclei/sec using a 400 nm long pass filter and chicken red blood cell (CRBC) nuclei as external standard for instrumental calibration and fluorescence reference during measurements, CRBC 2C DNA content = 2.15 pg [25]. DNA fluorescence was acquired as maximum fluorescence intensity (pulse height) and time-related parameters (fluorescence pulse area and width).…”
Section: Ploidy Estimation and Flow Cytometric Seed Screen (Fcss) Anamentioning
confidence: 99%
“…The main techniques currently employed for measuring DNA amount are flow cytometry [Geraci et al, 2007] and Feulgen image analysis densitometry (FIAD) [Hardie et al, 2002;Gregory and Shorthouse, 2003;Mendonça et al, 2010], although real time PCR has also been used [Wilhelm et al, 2003]. Doležel et al [1998] showed an excellent correspondence of genome size measurements performed by flow cytometry and FIAD.…”
mentioning
confidence: 99%